Infrequent disposition of the first metacarpal artery related to anastomoses of the superficial and deep systems of the hand - Bianchi, Homero Felipe (2020)
Fil: Bianchi, Homero Felipe. Instituto Universitario de Ciencias de la Salud. Fundación Barceló; Argentina.